1990
DOI: 10.2337/diacare.13.6.600
|View full text |Cite
|
Sign up to set email alerts
|

Lessons Learned From Molecular Biology of Insulin-Gene Mutations

Abstract: Studies on naturally occurring and man-made mutations in the insulin gene have provided new insights into insulin biosynthesis, action, and metabolism. Ten families have been identified in which one or more members have single-point mutations in their insulin genes that result in amino acid substitutions within the proinsulin molecule. Six of these cause the secretion of biologically defective insulin molecules due to changes within the A or B chains. Replacing A3-Val with Leu, B24-Phe with Ser, or B25-Phe wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
104
0
1

Year Published

1994
1994
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(105 citation statements)
references
References 41 publications
(60 reference statements)
0
104
0
1
Order By: Relevance
“…These findings suggest that a portion of nascent wild-type proinsulin is misfolded, and that ␤-cells are continuously in a situation close to ER "overload." Several point mutations that result in amino acid substitutions within the proinsulin molecules are known in humans, although those involving disulfide bonds have not been reported (23). Minor conformational changes of these human mutant proinsulins may induce ␤-cell dysfunction in the long term.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that a portion of nascent wild-type proinsulin is misfolded, and that ␤-cells are continuously in a situation close to ER "overload." Several point mutations that result in amino acid substitutions within the proinsulin molecules are known in humans, although those involving disulfide bonds have not been reported (23). Minor conformational changes of these human mutant proinsulins may induce ␤-cell dysfunction in the long term.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, mutation of the dibasic residues [294] and the use of active-site-directed peptides [296] has shown that type 1 (PC 1) and type 2 (PC2) enzymes require the presence of pairs of basic residues at their respective proinsulin cleavage sites. Finally, it has been shown that in some patients with familial hyperproinsulinaemia in which one of the basic amino acids at one of the cleavage sites has been altered, a partially cleaved proinsulin conversion intermediate is found in the circulation [297]. The cleavage specificity of proinsulin by PCI and PC2 has been analysed in more detail by co-transfection of rat insulin I into COS cells with human PCl and mouse PC2 [249].…”
Section: Furinmentioning
confidence: 99%
“…Abnormalities associated with NIDDM have been identified in insulin (2,3), insulin receptor (4,5), glucokinase ( MODY2 ) (6, 7), HNF-4 ␣ ( MODY1 ) (8), HNF-1 ␣ ( MODY3 ) (9), and mitochondrial genes (10,11). However, these abnormalities seem to be rare in the common form of NIDDM, and the major causes of NIDDM remain elusive.…”
Section: Introductionmentioning
confidence: 99%